A Study of the Correlation Between Intercultural Competence and Linguistic Competence at Postgraduate Level: From Theory to Practice - Safdar Habib,; Shakiaz Ahmed,; Nasim Gul ,; Mudassir Riaz,; Faisal Iqbal, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the correlation between intercultural competence and linguistic competence among postgraduate students. The current research also aims to explore how linguistic competence and intercultural competence contribute to each other in bidirectional way, what role is played by language proficiency in achieving intercultural competence at postgraduate level. Correspondingly, a quantitative survey is conducted to collect data from 35 postgraduate level students from diverse cultural backgrounds currently studying in prestigious universities, viz. Kohat University of Science and Technology, KUST, Kohat, National University of Modern Languages, NUML, Islamabad, COMSATS University Islamabad, Institute of Management Sciences (IMSciences), Peshawar, Pakistan, Lanzhou University, China and Xi’an Jiaotong University, China. The major findings of the study revealed that there lies a positive correlation between intercultural competence and linguistic competence. It was also found out that students with higher linguistic competence tend to have higher intercultural competence. Likewise, the study in hand, confirmed that students in the given context and at post graduate level demonstrate good understanding and sound awareness regarding their host culture, social norms, cultural values, customs, laws and traditions. Additionally, it was also highlighted by the study that students were found able enough to interact appropriately in various social situation i.e. aptly called pragmatic situations. Moreover, findings of the study have brought out significant implications for educators and policymakers by seeking to promote intercultural understandings/ awareness along with the focus on linguistic competence in higher education in order to prepare global citizens. Finally, the study emphasizes on intercultural knowledge to be imparted to the young language learners in Pakistan in order to overcome the chances of fluent fool phenomenon.